PENGARUH PENGGUNAAN MATRAS BIDANG MIRING TERHADAP PENINGKATAN KEMAMPUAN GULING DEPAN PADA MATA PELAJARAN PJOK DI SDN 2 NGLURUP PONOROGO - Mukti, Fiqhri Nugroho; Sunanto, Sunanto; Hidayat, Muhammad Thamrin; Susanto, Rudi Umar (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to evaluate the improvement of the ability and learning outcomes of the front roll through the application of a modification of the inclined plane mattress tool to students of SDN 2 Nglurup, Sampung District, Ponorogo District. The research was conducted using the Classroom Action Research (PTK) method and involved students in learning floor gymnastics. The results showed that the application of tool modifications for two cycles succeeded in improving students' abilities and learning outcomes in front roll movements. In cycle I, the level of the learning completeness only reached 37.5%, but after the tool modification approach in cycle II, the level of learning completeness increased to 87.5%. Thus, it can be concluded that the application of the modification of the inclined plane mattress tool in PJOK learning can improve the ability and learning outcomes of front roll in students of SDN 2 Nglurup, Sampung District, Ponorogo District.